ANALISIS TERHADAP MANFAAT INVESTASI DALAM PEMBANGUNAN EKONOMI - Tami Rusli (KEADILAN PROGRESIF, 2021)
With regard to development funding, the principle of independence cannot be fully implemented in national economic development. In order to sustain a rapidly growing economic development, substantial sources of funding are required. One of the economic development programs to accelerate Indonesia's economic recovery is to increase investment. The problem in this study is how the benefits of investment in Indonesia's economic development. The method in this study uses a normative and empirical juridical approach. Data sourced from secondary data and primary data. Data collection procedures using library research and field studies and qualitative data analysis. The results of the research show that the benefits of investment are a very important means of economic development, where we can see that there are 3 (three) issues in the world economy that support the Indonesian capital market to take advantage of investment opportunities, namely: Overall, world output is expected to experience a fairly good growth. World Bank predictions show that crisis countries in East Asia will have the second largest annual growth rate after Asia Pacific countries; The world's investment pattern has changed drastically, from direct investment to portfolio investment with an investment value of 31 times greater than transactions forgoods and services every year; The increasing role of market mechanisms in economic development, both in the goods market, money market and capital market.